Las imágenes de la Justicia en la Edad Moderna: génesis y análisis iconográfico - Rodríguez López, María Isabel (Anales de Historia del Arte, 2006)
Justice is a very complex conception, expressed as one of the more appraised human feelings in all the times and cultures. This work implies an approach to so much significant concept from an iconographyca point of view, attending to the origin, metamorphosis and analysis of iconographical attributes used by Modern Age artists as incarnation and expression of Justice´s idea. From this iconic perspective as departure, it is possible to understand the course of thoughts, ethic values and ways of life in the Renaissance and Baroque european society and the iconographical influence come from Antiquity and Middle Ages.